2004
DOI: 10.1088/0953-2048/17/8/006
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the microstructure and critical current densities of Bi-2212 round wires with a precisely controlled heat treatment

Abstract: We succeeded in obtaining excellent Jc values of Bi2212 multifilamentary round wire with a precisely controlled heat treatment. The heat treatment, which consisted of melt solidification and a subsequent slow-cooling process, was applied to Bi-2212 superconductors. The Ic values of Bi-2212 wires heat treated with a maximum processing temperature Tmax below the optimum Tmax of Bi-2212 were zero, while high Ic values of 450 A, Jc = 280 kA cm−2 at 4.2 K and 10 T magnetic field, were obtained in a very narrow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 7 publications
4
29
0
Order By: Relevance
“…This is extremely important for a reproducible, homogeneous production of wires in large lengths. A dramatically increased critical current (peak effect) within a few tenth of a degree at the beginning of melting the 2212 phase as was found by Matsumoto et al [3] is only weakly pronounced. Rikel et al [13] confirmed this behavior but, however, it is in contrast to earlier papers in which a pronounced peak effect was shown [2,3].…”
Section: Single Wiressupporting
confidence: 53%
See 3 more Smart Citations
“…This is extremely important for a reproducible, homogeneous production of wires in large lengths. A dramatically increased critical current (peak effect) within a few tenth of a degree at the beginning of melting the 2212 phase as was found by Matsumoto et al [3] is only weakly pronounced. Rikel et al [13] confirmed this behavior but, however, it is in contrast to earlier papers in which a pronounced peak effect was shown [2,3].…”
Section: Single Wiressupporting
confidence: 53%
“…A dramatically increased critical current (peak effect) within a few tenth of a degree at the beginning of melting the 2212 phase as was found by Matsumoto et al [3] is only weakly pronounced. Rikel et al [13] confirmed this behavior but, however, it is in contrast to earlier papers in which a pronounced peak effect was shown [2,3]. For a better comparison with literature data and to see the influence of different wire diameters, the critical current density is shown via T max in figure 2.…”
Section: Single Wiressupporting
confidence: 53%
See 2 more Smart Citations
“…The powder-in-tube (PIT) process is used to fabricate high-performance multi-filament superconducting wires of Nb 3 Sn [1], Bi-2212 [2], and MbB 2 [3,4]. While the specific powders, the synthesis routes, the sheath metal, and the PIT processing after powder filling are different in each case and indeed among the several practitioners of each superconductor, there is a common element that paces the ability to fabricate drawn multifilamentary composites of these materials.…”
Section: Importance Of Powder Size Distribution In Pit Superconductormentioning
confidence: 99%